P.S. Postilla : A parallel study on the Apostles' Clubhouse in the Reykjavik Art Museum. - Aevarsdottir, Oddny Eir (Reykjavik : Reykjavik Art Museum, 2008)
Arnardóttir, Hrafnhildur ; Arnason, Magnus ; Eiriksdottir, Kristin ; Finna & Brynhildur ; Gudnadottir, Björk ; Gunnarsdottir, Asdis Sif ; Halldorsson, David Örn ; Kjartansson, Ragnar ; Magnadottir, Ingibjörg ; Sigurdardóttir, Sirra Sigrún ; Sigurdardottur, Sigga Björg ; Thorsson, Helgi
Engels
Exhibition. Apostles' Clubhouse. Reykjavik Art Museum Reykjavik. 01.09.2006 -22.10.2006
boek
Keywords: IJsland